Large band-gap copolymers based on a 1, 2, 5, 6-naphthalenediimide unit for polymer solar cells with high open circuit voltages and power conversion efficiencies. Issue 19 (25th April 2016) - Li, Zuojia; Feng, Kui; Liu, Jiang; Mei, Jun; Li, Ying; Peng, Qiang
Abstract : Large band-gap copolymers based on 1, 2, 5, 6-naphthalenediimide were developed for photovoltaic applications. A PCE of 6.35% was obtained by gradually optimizing the morphology of active layers. Abstract : In this paper, we developed new types of efficient large band-gap copolymers, PBDTA-INDI andPBDTT-INDI, based on a 1, 2, 5, 6-naphthalenediimide (1, 2, 5, 6-INDI) acceptor block for polymer solar cells (PSCs).PBDTA-INDI andPBDTT-INDI have band-gaps of 2.0 eV and 1.98 eV, which are comparable to that of the widely studied P3HT. Both copolymers also possess low-lying HOMO energy levels below −5.40 eV, which are expected to lead to high V oc values for their PSCs. The XRD analysis indicates their good molecular packing properties. Their photovoltaic properties were evaluated by using conventional devices with a structure of ITO/PEDOT:PSS/copolymer:PC71 BM/Ca/Al fabricated under different conditions. ThePBDTA-INDI andPBDTT-INDI devices showed a relatively poor performance with PCEs of 2.83% and 4.13% with pure chlorobenzene (CB) solvent by adding 3 vol% DIO. The device performance was largely improved by using a co-solvent of CB and chloroform (CF) with increased PCEs of 3.76% and 5.01%. After employing the thermal annealing (TA) treatment, the PCEs ofPBDTA-INDI andPBDTT-INDI devices were finally increased to 5.04% and 6.35%. The gradually increased device performance would be attributed to the gradually optimized morphology of the related active blend films, which significantly induced a higher EQE response and hole mobility, giving rise to higher J sc and FF values. Our results indicated that 1, 2, 5, 6-naphthalenediimide is a promising acceptor block to build high-performance large band-gap copolymers for potential applications in single-junction and tandem PSCs in the future.